Trianon hatása a Bánság városhálózatára - Kókai, Sándor (Közép-Európai Közlemények, 2014)
In the last decade the internal migration waves correlated with border changes and the social and economical pursuit of successor States, and the assimilation process also significantly contributed to the national homogenisation of the previously multiethnical settlements and the continuous space loss of minor ethnical groups. The regions near Trianon border and small towns both homoge- nisated, therefore the Bánság degraded to a meeting point of three different culture, language and religion divided by the nations’ borders, which means a serious step back compared to the early decades of the 20th century. This study prooves that the cumulatively handicapped Bánság region and its settlements stepped into the 21st century with many contradiction. During last fifty years in the Bánság bigger cities - where multilingual society were typical before Trianon - the German and Hungarian language disappeared, not mentioning the other ethnic groups. As a result of social and economical process nowadays the decline of nationalities is continuous in most of the Bánság settlements.